Effect of Fuel Properties of Kerosene on Deposit Accumulation: Deposit Accumulation on Wick during Wick Combustion - HAYASHIDA, Kazuhiro; ARAI, Masataka; HAJI, Katsuhiko; ISHITANI, Hiromi (Journal of Environment and Engineering, 2011)
Effect of fuel properties of kerosene on deposit accumulation was studied experimentally. Five types of kerosene, which distillation and composition properties were different, were used as the test fuel. Deposit accumulation processes were investigated by using wick combustion burner. Deposit accumulation rate was estimated from the mass of deposit which accumulated on wick and the fuel consumption. As the results, it was confirmed that the deposit accumulation rate increased with the content of aromatic hydrocarbons and naphtheno benzenes. Main component of the deposit was heavy hydrocarbons formed by thermal decomposition and polycondensation of the fuel within the wick. To estimate the effect of peroxide on deposit accumulation, test fuels which contain peroxide generated by sun exposure were used. The peroxide-containing fuels significantly increased the deposit mass than normal fuels.